The presentation of Indonesia’s traditional dances a study of Tari Saman (Aceh) and Tari Kecak (Bali) - Handayani, Bintang; Reyes, Aida Yarira; Kosnin, Ruzanifah; Bah Simpong, Derweanna (2021)
Theobjectives of this essay are twofold: firstly, to provide a critical evaluation of the usefulness of Indonesia’s traditional dances in enriching its national profile; and secondly, to assess some practical implications associated with utilising traditional dances as a predictor for a nation’s personification. It is a reflective study that relies on a structured review approach. The study suggests that traditional dances, revolving around the formation of religiosity as an expression of praise to God, are not only embedded with authentic shared values, but also attributed to collective cultural production. The multi-layered rhythmic vocal canting, not to praise God but more likely as dramatic actions. Cultural production in this setting enriches a nation’spersonification that is taken in other domain as a predictor attribute of a nation’s brand image. Some directions for future research, limitations, and concluding remarks are provided.